Pemberdayaan Siswa melalui Kelompok Edukasi Pencegahan Stunting di SMA 7 Samarinda - Rahayu, Eka Putri; Chifdillah, Nino Adib; Ardyanti, Dian (Penerbit Goodwood, 2024)
Purpose: The aim of this activity was to improve the behavioral domain of students at SMAN 7 Samarinda regarding stunting prevention through student empowerment. Methodology: The method of implementing activities was divided into five stages. The first stage was the formation of an educational group consisting of school students. The second stage was health education about stunting and its prevention for educational groups. The third stage was training in health education methods and techniques as well as physical examinations for the education group. The fourth stage was assistance in preparing work programs and implementing education for students at school. The fifth stage was an evaluation of the implementation and sustainability of the working group's work program Results: The results of the activity showed that there was an increase in the percentage of students who had good knowledge by 62% and a positive attitude reaching 76.9% at the end of the activity. Wilcoxon test analysis produced a p-value of 0.000 for the knowledge variable and 0.000 for the attitude variable. Conclusions: The formation and mentoring of an educational group for stunting prevention among high school students implement health promotion strategies through five stages of activities. Health education provided by the established stunting prevention education group has successfully increased students' knowledge about stunting and its prevention. Limitations: Student empowerment was effective in increasing school students' knowledge towards stunting prevention since adolescence. Contribution: This community service increases the knowledge of students to prevent health diseases, specifically stunting.